Some factors related to the performance in the NCEE by the 1976-1978 graduates of the San Pablo City High School - Bienvenida, Mila C. 1944-
This study aimed to determine whether a relationship exists between performance in the NCEE and some intellective and non-intellective factors. The variables investigated were the general average, parents' educational attainment, and student's aspiration. To test the significance of the relationship, the Multiple Regression Analysis was employed for intellective factor while the chi square test was used for non-intellective factors. Results showed that academic achievement had the highest predictive ability among the variables. NCEE-GSA and students' level of aspiration also gave a higher correlation value than GSA and parental education. Parental education, when taken independently of other indices of socio-economic status, did not correlate significantly with NCEE scores.